Expanding the genetic and phenotypic spectrum of CHD2‐related disease: From early neurodevelopmental disorders to adult‐onset epilepsy. Issue 2 (29th October 2021) - De Maria, Beatrice; Balestrini, Simona; Mei, Davide; Melani, Federico; Pellacani, Simona; Pisano, Tiziana; Rosati, Anna; Scaturro, Giusi M.; Giordano, Lucio; Cantalupo, Gaetano; Fontana, Elena; Zammarchi, Cristina; et al.
Abstract: CHD2 encodes the chromodomain helicase DNA‐binding protein 2, an ATP‐dependent enzyme that acts as a chromatin remodeler. CHD2 pathogenic variants have been associated with various early onset phenotypes including developmental and epileptic encephalopathy, self‐limiting or pharmacoresponsive epilepsies and neurodevelopmental disorders without epilepsy. We reviewed 84 previously reported patients carrying 76 different CHD2 pathogenic or likely pathogenic variants and describe 18 unreported patients carrying 12 novel pathogenic or likely pathogenic variants, two recurrent likely pathogenic variants (in two patients each), three previously reported pathogenic variants, one gross deletion. We also describe a novel phenotype of adult‐onset pharmacoresistant epilepsy, associated with a novel CHD2 missense likely pathogenic variant, located in an interdomain region. A combined review of previously published and our own observations indicates that although most patients (72.5%) carry truncating CHD2 pathogenic variants, CHD2 ‐related phenotypes encompass a wide spectrum of conditions with developmental delay/intellectual disability (ID), including prominent language impairment, attention deficit hyperactivity disorder and autistic spectrum disorder. Epilepsy is present in 92% of patients with a median age at seizure onset of 2 years and 6 months. Generalized epilepsy types are prevalent and account for 75.5% of all epilepsies, with photosensitivity being a common feature and adult‐onset nonsyndromic epilepsy a rare presentation. No clear genotype–phenotype correlation has emerged.